Model for photoinduced bending of slender molecular crystals - Nath, Naba K; Pejov, Ljupčo; Nichols, Shane M; Hu, Chunhua; Saleh, Na'il; Kahr, Bart; Naumov, Panče (American Chemical Society (ACS), 2014)
The growing realization that photoinduced bending of slender photoreactive single crystals is surprisingly common has inspired researchers to control crystal motility for actuation. However, new mechanically responsive crystals are reported at a greater rate than their quantitative photophysical characterization; a quantitative identification of measurable parameters and molecular-scale factors that determine the mechanical response has yet to be established. Herein, a simple mathematical description of the quasi-static and time-dependent photoinduced bending of macroscopic single crystals is provided. This kinetic model goes beyond the approximate treatment of a bending crystal as a simple composite bilayer. It includes alternative pathways for excited-state decay and provides a more accurate description of the bending by accounting for the spatial gradient in the product/reactant ratio. A new crystal form (space group P21/n) of the photoresponsive azo-dye Disperse Red 1 (DR1) is analyzed within the constraints of the aforementioned model. The crystal bending kinetics depends on intrinsic factors (crystal size) and external factors (excitation time, direction, and intensity).